Bridging Faith and Reason: Childhood Character Education Between Islamic Ethics and Humanistic Values - Masnur Putra Halilintar; Zohaib Hassan Sain; Uthman Shehu Lawal; Shahzadi Hina (Yayasan Mabadi Iqtishad Al Islami, 2026)
This paper offers a comparative analysis of character education through the lens of Islamic and secular humanistic paradigms. Recognizing the increasing cultural and religious diversity in contemporary educational settings, the study emphasizes the importance of an integrative approach that respects both spiritual and rational ethical frameworks. Islamic character education centers on virtues derived from divine guidance, fostering a moral compass anchored in faith, while secular humanistic education promotes critical thinking, autonomy, and universal ethical principles grounded in reason and empathy. By synthesizing these approaches, educators can cultivate learners’ moral resilience, empathy, and ethical commitment within pluralistic societies. The paper further highlights the benefits of intercultural dialogue, pedagogical innovation, and cultural competence for teachers, parents, and communities in supporting holistic moral development. Ultimately, the integration of these models enriches character education, preparing students to become ethically responsible and socially engaged citizens in globalized contexts